Koszty transakcyjne w agrobiznesie w Polsce po roku 1990 - Czyżewski, Bazyli (Transaction Costs in Polish Agribusiness after Year 1990, 2005)
The aim of this article is to determine a tendency of transaction costs in Polish agribusiness comparing them to the country-wide situation. The level of transaction costs makes possible to define a direction of institutional sphere evolution. Rising costs mean that ineffective structures are still functioning and institutional hysteresis exerts influence on economy. However, dropping costs indicate a positive selection process - in that case only CAP funds will be allocated efficiently.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 1, s. 137-142